Strategies to Strengthen Religious Moderation in Universities - Sultoni, Achmad; Nasih, Ahmad Munjin; Thoriquttyas, Titis; Yani, Achmad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to examine the strategies of public universities to strengthen religious moderation on campuses to foster religious tolerance and nationalism among campus communities. Qualitative methods were used to obtain data for analysis. The subject of the study was Universitas Negeri Malang (UM), a large state university in East Java that offers various religious moderation programs, including Griya Moderasi Beragama dan Bela Negara (GMBBN, House of Religious Moderation and State Defense). The study was conducted from September 2024 to February 2025 using observation, interviews, and documentation techniques. The data were analyzed using Miles and Huberman's interactive analysis: data collection, data reduction, data display, and conclusion/verification. The research revealed nine strategies to strengthen religious moderation in campus, namely: establishing institutions of religious moderation, inserting religious moderation values into lectures, conducting research and community service on religious moderation, religious mentoring, establishing and guiding religious student activity units, scientific studies on religious moderation, non-academic activities on religious moderation, dissemination of media and content of religious moderation, and places of worship to promote religious moderation.